2017
DOI: 10.1039/c7ce00994a
|View full text |Cite
|
Sign up to set email alerts
|

Novel amine templated three-dimensional zinc-organophosphonates with variable pore-openings

Abstract: Amine templated three-dimensional zinc-organophosphates with different ring sizes have been obtained by varying the organic amine molecules. The figure shows the various net structures obtained during the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…Considering the similarity between inorganic phosphates (or phosphites) and organophosphonates, the organoamines-directed assembly is also applicable to the metal phosphonate. An overview of literature indicated that the early investigated organoamines mainly focus on the small rigid/flexible species, just exampled by heterocyclic amine and aliphatic amine. By contrast, the long aliphatic amine (the total atoms for the chain larger than eight) and large heterocyclic amine (the N -heterocycle larger than three) are relatively less investigated. This is not surprising for several reasons, one of which may be partly due to the fact that such long-chain flexible organic amines are easily decomposed under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the similarity between inorganic phosphates (or phosphites) and organophosphonates, the organoamines-directed assembly is also applicable to the metal phosphonate. An overview of literature indicated that the early investigated organoamines mainly focus on the small rigid/flexible species, just exampled by heterocyclic amine and aliphatic amine. By contrast, the long aliphatic amine (the total atoms for the chain larger than eight) and large heterocyclic amine (the N -heterocycle larger than three) are relatively less investigated. This is not surprising for several reasons, one of which may be partly due to the fact that such long-chain flexible organic amines are easily decomposed under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Of late, the advancement of transition-metal-based materials such as oxides, nitrides, sulfides, selenides, hydroxides, phosphides, phosphates, and various composite materials are considered as excellent catalysts for boosting electrochemical water splitting performance by replacing precious platinum/iridium catalysts. The selection of flexible phosphonate groups along with incorporation of variable templated organoamines in hybrid metal phosphonate structures not only lead to a variety of structures but also serve as charge separators with modulated catalytic activity. Interestingly, the lower dimensional transition metal phosphonate are often exciting for their strange magnetic behaviors and field-induced transitions. However, among plentiful stimulating properties of hybrid metal phosphonates, the electrocatalytic water splitting reaction remains less explored so far. With our continuous effort with metal phosphonates, herein we have isolated two new hybrid one-dimensional transition-metal phosphonate chain structures with templated TETA through a hydrothermal pathway (i.e., [H 2 TETA]­[M­(H 2 hedp) 2 ]·2H 2 O, where M = Co for I , Ni for II ; H 4 hedp = 1-hydroxyethane-1,1-diphosphonic acid; TETA = triethylenetetramine) for the investigation of their electrochemical behaviors toward OER and HER. The present study not only explores the potential of any low cost bifunctional OER/HER catalyst designed by organophosphonate ligands but also exposes a promising avenue to explore stable, efficient, and precious-metal-free lower-dimensional framework structures as electrocatalysts.…”
mentioning
confidence: 99%
“…Silver­(I) ions, by their inherent chemical nature of irregular coordination number and geometry, are best suited for isolating fascinating hybrid frameworks. However, the amine-templated silver­(I) phosphonate frameworks have not been thoroughly investigated to date. In continuation of our earlier work, we have synthesized two silver­(I) diphosphonate layer structures with templated piperazine, viz, [C 4 H 12 N 2 ]­[Ag 4 (hedp) 2 ] ( I ) and [C 4 H 12 N 2 ]­[Ag 10 (hedp) 4 (H 2 O) 2 ]·2H 2 O ( II ; hedp = 1-hydroxyethane-1,1-diphosphonic acid), with variable silver clusters and exciting properties. For the first time, extremely high dielectric permittivity values are observed with the present 2D semiconducting silver-phosphonate frameworks.…”
mentioning
confidence: 99%